2006
DOI: 10.1093/geronb/61.5.p285
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Learning and Aging: Combined Effects of Irrelevant Speech, Interstimulus Interval, and Education

Abstract: Older or lower educated individuals may be less able than younger or higher educated individuals to inhibit irrelevant speech when learning new visual information. In Experiment 1, we investigated the effects of age (four groups), educational attainment (low or high), and verbal noise (spoken words or silence) on word-learning performance in 230 individuals aged 24 to 76 years. Performance was negatively affected by age, lower education, and irrelevant speech, but there were no interactions between age group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Consistent with this, Chao and Knight (1997) showed that multiple auditory tone distractors presented during a 9 sec or longer, but not shorter, delay interval did indeed generate worse auditory WM in older adults. Meijer et al (2006) showed similar findings using a sequence of auditory distractions, presented either rapidly or slowly, with greater age-related impacts on WM observed for the more challenging rapid distractor presentations. These studies raise the possibility that higher interference loads in the form of greater number of interfering stimuli, greater stimulus congruity and hence confusability between the WM and interference stimuli, and greater complexity of the interference task may indeed show differentially greater impacts on WM performance in older relative to younger adults.…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with this, Chao and Knight (1997) showed that multiple auditory tone distractors presented during a 9 sec or longer, but not shorter, delay interval did indeed generate worse auditory WM in older adults. Meijer et al (2006) showed similar findings using a sequence of auditory distractions, presented either rapidly or slowly, with greater age-related impacts on WM observed for the more challenging rapid distractor presentations. These studies raise the possibility that higher interference loads in the form of greater number of interfering stimuli, greater stimulus congruity and hence confusability between the WM and interference stimuli, and greater complexity of the interference task may indeed show differentially greater impacts on WM performance in older relative to younger adults.…”
Section: Discussionsupporting
confidence: 60%
“…Nevertheless, an interaction between age and the level of interference might emerge if task complexity is systematically increased. Meijer et al (2006), for instance, found greater disruptive effects of background speech on verbal learning in older than in young individuals if they decreased the time interval between words in the encoding phase of a verbal learning task.…”
Section: Discussionmentioning
confidence: 99%
“…An early study by Molander and Bäckman (1990) with very few participants (six young and six older adults) revealed that motor performance of older people is more affected by verbal than nonverbal noise, whereas motor performance of younger adults is equally affected by the two types of noise. Meijer, De Groot, Van Boxtel, Van Gerven, and Jolles (2006) found episodic memory of older adults to be more affected by irrelevant speech only after decreasing the interstimulus interval in a verbal learning task. In most studies, however, no interaction was found between noise and age.…”
mentioning
confidence: 88%
“…Pilot testing indicated that older adults required a longer processing time than younger adults for this task, and the inter stimulus interval (ISI) was increased to 1500 ms ( Wong and Perrachione, 2007 ). Longer ISIs have been shown to be more beneficial for older than younger adults ( Meijer et al, 2006 ), thought to be due to reduced speed of processing in older adults. Performance on the PCPT has been linked to Mandarin lexical tone learning performance in younger adults ( Wong and Perrachione, 2007 ; Chandrasekaran et al, 2010 ; Perrachione et al, 2011 ; Ingvalson et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%